SWAMEDIKASI PENGGUNAAN OBAT ALERGI SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN MASYARAKAT DI DESA SEJAHTERA KECAMATAN PALOLO: SWAMEDIKASI PENGGUNAAN OBAT ALERGI SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN MASYARAKAT DI DESA SEJAHTERA KECAMATAN PALOLO - indah kurnia utami; Ratna Ika Yususf; niluh puspita dewi; Syafika Alaydrus (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Self-medication or what is known as self-medication is one of the actions that are often taken by the community to treat skin disorders. Based on a systematic review, it is known that the prevalence of self-medication in skin diseases ranges from 6-44%. Research in Togo, Africa found that 91.1% of people with skin disorders who seek treatment at health services have self-medicated before going to health services, while research conducted in Jakarta showed 44.64% of people were self-medicating for skin diseases with modern or traditional medicines. Allergies are reactions of the human immune system to certain objects, which should not cause reactions in other people's bodies. The reaction can appear in the form of a runny nose, itchy skin rash, or even shortness of breath. The drugs used by the public in self-medication of skin diseases are oral and topical drugs, including preparations containing corticosteroids, antibiotics and antifungals, a combination of salicylic acid and benzoic acid. Self-medication behavior can be influenced by knowledge, sociodemographic characteristics, family and advertising. Based on research, knowledge is the most significant factor influencing self-medication behavior.